Aerosol formation by heterogeneous reactions in ammonia-based WFGD systems. (December 2017) - Huang, Rongting; Luo, Lvyuan; Zhou, Xincheng; Pan, Danping; Yang, Linjun
Abstract: Aerosol problems in the ammonia-based wet flue gas desulfurization (ab-WFGD) system are of major concern in the field of atmospheric science. Previous studies stated that the heterogeneous reactions of SO2 -H2 O-NH3 (the SO2 reactions) are one of the major sources of the aerosol emission from ab-WFGD systems. In this paper, the aerosol formation from the SO3 relating reactions (the SO3 reactions) was investigated experimentally. The results were compared with those from the SO2 reactions to distinguish the contributions they made to the aerosol emission. The influences of the corresponding parameters, such as the moisture content, the reaction temperature, and the NH3 -to-SO2 /SO3 ratio (NH3 /SOx ), on the aerosol formation were also explored. The results show that although the SO3 concentration is lower than the SO2 concentration, the aerosols formed by the SO3 reactions are much more than those generated from the SO2 reactions (numerical concentration). More than 90% of the aerosols are ultrafine particles. The aerosols formed from the SO2 reactions are smaller than those from the SO3 reactions. When the reaction temperatures increase above 65 °C, the SO2 reactions are hindered significantly while the SO3 reactions are barely influenced. Higher moisture content can enhance the aerosol formation from the SO2 reactions, but can hardly affect the SO3 reactions. The increment of the NH3 /SOx ratios boosts both the SO2 reactions and the SO3 reactions. When the NH3 /SO3 reached 2.0 and more, the aerosol formation from the SO3 reactions stops increasing while the aerosol concentration in the SO2 reactions keeps growing. Moreover, the parameter optimization methods were applied in a pilot-scale ab-WFGD system to evaluate the efficiency for aerosol emission control. The results show that decreasing the flue gas temperature before WFGD to around 80 °C can reduce the aerosol emission by 20%. Adjusting the desulfurization solution pH to about 4.5 can decrease the aerosol emission by 45% while keeping the desulfurization efficiency above 95%. Highlights: Aerosols formed in SO3 reactions are more than those in SO2 reactions. Aerosols formed by heterogeneous reactions are mostly ultrafine. SO2 reactions are inhibited at high temperatures. Heterogeneous reactions are boosted at high NH3 /SOx ratios. Adjusting flue gas temperature to 80 ℃ help to reduce the aerosol emission.